Biodegradable stretch film and preparation method thereof

By using toughening agents prepared by the reaction of phenylalanine, tyrosine and gum arabic in the biodegradable winding film, combined with poly-butylene terephthalate-butylene adipate, polylactic acid and polypropylene carbonate and other materials, the shortcomings of the PBAT-based biodegradable winding film in terms of stretchability and tensile resistance are solved, and high mechanical properties and low-cost biodegradable winding film preparation are achieved.

CN119119696BActive Publication Date: 2025-03-11ZIBO LONGSHA POLYMER MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411616169.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-11
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing PBAT-based biodegradable wound films have shortcomings in terms of stretchability and tensile resistance, which limits its application scenarios. At the same time, the multi-layer coextrusion preparation method increases production costs.

Method used

A toughening agent prepared by the reaction of phenylalanine, tyrosine and gum arabic, combined with poly-butylene terephthalate-butylene adipate, polylactic acid and polypropylene carbonate, is used to prepare a biodegradable wound film through extrusion granulation and casting film formation processes.

Benefits of technology

The longitudinal and transverse tensile strength of the biodegradable wound film is significantly improved, the elongation of break is significantly improved, and the mechanical properties are better than those of films without toughening agents. At the same time, the production cost is reduced, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer films, and specifically relates to a biodegradable wrapping film and a preparation method thereof. The biodegradable wrapping film comprises the following components: 70-85 parts of PBAT, 10-30 parts of polylactic acid, 5-10 parts of polypropylene carbonate, 10-15 parts of toughening agent, 5-15 parts of plasticizer, 1-2 parts of light stabilizer, and 0.1-0.3 parts of antioxidant; wherein the toughening agent is prepared by reacting phenylalanine, tyrosine and gum arabic. The preparation method is to prepare the toughening agent in advance; stir PBAT, polylactic acid, polypropylene carbonate, plasticizer and antioxidant once, continue to add toughening agent and light stabilizer for secondary stirring, and then prepare the biodegradable wrapping film by extrusion granulation and cast film. The present invention improves the stretchability and tensile strength of the biodegradable wrapping film based on PBAT by adding a homemade toughening agent, and at the same time, by granulation and one-time cast extrusion film making, the preparation method is simple to operate, low cost, and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer films, and in particular relates to a biodegradable wrapping film and a preparation method thereof. Background Art

[0002] Stretch film is a special film product mainly used in agriculture, packaging, logistics and other fields. Currently, the common material of stretch film is low-density polyethylene, whose main characteristics are good stretchability, excellent puncture resistance and tear resistance, and it also has large resilience and lasting tightening force; but the molecular structure of polyethylene is relatively regular and has high crystallinity, which leads to its slow degradation rate in the natural environment, easily causing white pollution and damaging the environment. Although the biodegradability can be improved by adding some biodegradable materials such as starch-based materials, polylactic acid, etc., this sometimes has an adverse effect on the transparency and tensile strength of the stretch film.

[0003] Studies have found that enzymes secreted by microorganisms in the natural environment will specifically attach to the ester bonds of polybutylene terephthalate-adipate (PBAT) and catalyze the hydrolysis of PBAT into a series of oligomers and monomers. These oligomers and monomers have low biological toxicity and are more easily degraded. Therefore, as environmental protection is increasingly valued, PBAT wrapping film has a wide range of applications in agriculture, packaging, logistics and other fields. However, compared with low-density polyethylene, PBAT materials have poor stretchability and tensile strength, which limits the application scenarios of PBAT materials. Therefore, improving the stretchability and tensile strength of PBAT materials has become one of the main research directions of technicians in the field of wrapping films.

[0004] Chinese patent CN114656886A discloses a fully biodegradable wrapping film and a preparation method thereof. The fully biodegradable wrapping film comprises, from top to bottom, a bonding layer, a supporting layer and a bonding layer; the materials required for the supporting layer include, by weight: 5-20 parts of polylactic acid, 40-70 parts of polybutylene adipate-terephthalate, 5-20 parts of polymethylethylene carbonate, 5-10 parts of polycaprolactone, 0.1-3 parts of a chain extender, 0.1-2 parts of an antioxidant and 0.5-5 parts of a lubricant; the materials required for the bonding layer include, by weight: 50-80 parts of polybutylene adipate-terephthalate, 5-30 parts of polymethylethylene carbonate, 5-10 parts of polycaprolactone, 1-5 parts of polyisobutylene, 0.1-3 parts of a chain extender, 0.1-2 parts of an antioxidant and 0.5-5 parts of a lubricant. This patent only uses an adhesive layer, which may result in insufficient mechanical properties. Therefore, a support layer is inserted between the adhesive layers, and a multi-layer co-extrusion method is used to prepare a fully biodegradable wrapping film.

[0005] This patent uses multi-layer co-extrusion to form the film, but compared with cast extrusion, multi-layer co-extrusion requires a more precise die head, a more accurate temperature and pressure control system, and higher requirements for the viscosity and fluidity control of the raw materials, and the production cost will increase accordingly.

[0006] It can be found that the existing PBAT-based biodegradable stretch film still has many shortcomings in terms of mechanical properties such as stretchability and tensile strength, as well as cost; technicians hope to find solutions to overcome the above shortcomings, so as to promote the promotion and use of biodegradable stretch film. Summary of the invention

[0007] The object of the present invention is to provide a biodegradable stretch film to further improve the stretchability and tensile strength of the biodegradable stretch film based on PBAT; the present invention also provides a preparation method, which is easy to operate.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] The biodegradable wrapping film of the present invention is made of the following components in parts by mass: 70-85 parts of polybutylene terephthalate-adipate, 10-30 parts of polylactic acid, 5-10 parts of polypropylene carbonate, 10-15 parts of a toughening agent, 5-15 parts of a plasticizer, 1-2 parts of a light stabilizer, and 0.1-0.3 parts of an antioxidant; wherein the toughening agent is prepared by reacting phenylalanine, tyrosine, and gum arabic.

[0010] in:

[0011] The mass ratio of the phenylalanine, tyrosine and gum arabic is 1:1.2:0.4-0.7.

[0012] The reaction temperature of the phenylalanine, tyrosine and gum arabic is 160-170° C., and the reaction time is 70-110 min.

[0013] The reaction requires the addition of a catalyst and a water absorbent.

[0014] The catalyst is nitrous acid, and the added amount is 0.1-0.3% of the mass of gum arabic; the water absorbent is a silica gel desiccant, and the added amount is 1-3% of the mass of gum arabic.

[0015] The polybutylene terephthalate-adipate is one or more of 1200F, BT12-203, T16 or ECO-A05; the polylactic acid is one or both of F2332 or C2203F; the polypropylene carbonate is one or both of 8801 or HF901; the plasticizer is one or more of epoxy soybean oil, acetyl tributyl citrate, and tributyl citrate; the light stabilizer is one or both of UV770 or UV292; and the antioxidant is one or both of antioxidant 168 or antioxidant 1098.

[0016] The method for preparing the biodegradable stretch film of the present invention comprises the following steps:

[0017] (1) Add phenylalanine and tyrosine to gum arabic to directly react and obtain a toughening agent;

[0018] (2) polybutylene terephthalate-adipate, polylactic acid, polypropylene carbonate, plasticizer and antioxidant are stirred once, and toughening agent and light stabilizer are added for secondary stirring, and then extrusion granulation is performed to finally obtain a stretch film masterbatch;

[0019] (3) Casting the stretch film masterbatch into a film to produce a biodegradable stretch film.

[0020] In the step (2), the first stirring temperature is 165-175°C, the first stirring time is 20-30 min, and the second stirring time is 5-10 min.

[0021] In the step (3), a twin-screw extruder is used for extrusion granulation, and the barrel temperature of the twin-screw extruder is 180-195°C and the head temperature is 165-170°C.

[0022] In the step (3), a single-screw cast film extruder is used for film casting, and the barrel temperature of the single-screw cast film extruder is 180-195°C, and the head temperature is 170-175°C.

[0023] The beneficial effects of the present invention are as follows:

[0024] (1) The present invention adds a self-made toughening agent to improve the stretchability and tensile strength of the biodegradable wrapping film: the carboxyl groups in phenylalanine and tyrosine can undergo an esterification reaction with the hydroxyl groups in gum arabic and be grafted onto the gum arabic, and the grafted phenylalanine and tyrosine undergo a dehydration condensation reaction to form a cross-linking system. The cross-linking system contains a large number of hydrogen bond donors (such as ester groups, amide groups and hydroxyl groups, among which the hydroxyl groups on gum arabic account for the majority of the hydrogen bond donors). The compatibility between the toughening agent and PBAT, polylactic acid or polypropylene carbonate can be improved through hydrogen bonding. At the same time, the hydrogen bonding of hydroxyl groups can guide the arrangement of macromolecular chains such as PBAT to be more regular and uniform. This regular and uniform molecular chain arrangement helps to improve the overall mechanical properties of the biodegradable wrapping film, so that the material can more evenly withstand and disperse stress when subjected to external forces, reducing the occurrence of local tearing.

[0025] Since phenylalanine and tyrosine have a β-folded conformation, the molecules have a certain degree of elasticity and flexibility; in addition, both phenylalanine and tyrosine side chains contain benzene rings that provide steric hindrance and rigidity. Therefore, after being grafted onto gum arabic, the cross-linking system can balance flexibility and rigidity, which is manifested macroscopically as good tensile strength on the one hand; on the other hand, under the action of tension, the membrane structure can still be maintained intact without wrinkles and local tears after a large deformation, that is, the elongation at break is good.

[0026] In addition, tyrosine and phenylalanine are both natural amino acids, and gum arabic is a natural polysaccharide. The three have good biodegradability and biocompatibility; gum arabic has a highly branched structure and excellent compatibility, showing good toughness, so it can be used as a toughening agent skeleton. The addition of tyrosine, phenylalanine and gum arabic in appropriate proportions will not affect the biodegradability of the biodegradable stretch film on the basis of improving the mechanical properties of the biodegradable stretch film.

[0027] (2) The raw materials required for the biodegradable stretch film of the present invention are readily available, moderately priced and easy to process; at the same time, the preparation method of the present invention forms the film by granulation and direct one-time cast extrusion, and the film-making operation is simple, does not require the installation of additional precision equipment, has low cost, and is suitable for large-scale production.

[0028] (3) Experiments have shown that the biodegradable wrapping film made using the self-made toughening agent of the present invention has a longitudinal tensile strength of >70MPa, a transverse tensile strength of >40Mpa, a longitudinal elongation at break of >600%, and a transverse elongation at break of >900%. Compared with the biodegradable film without the toughening agent of the present invention, it has a greater advantage in tensile strength and elongation at break. DETAILED DESCRIPTION

[0029] The following is a simplified description, in which polybutylene terephthalate-adipate is referred to as PBAT, polylactic acid is referred to as PLA, and polypropylene carbonate is referred to as PPC.

[0030] PBAT: Brand 1200F, produced by BASF of Germany; Brand BT12-203, produced by Changchun Chemical Industry of Taiwan, China; Brand T16, produced by Wanhua Chemical; Brand ECO-A05, produced by Changchun Chemical Industry of Taiwan, China.

[0031] PLA: Brand F2332, produced by BASF, Germany; Brand C2203F, produced by BASF, Germany.

[0032] PPC: Brand 8801, supplied by Dongguan Kaixili Plastic Raw Materials Co., Ltd.; Brand HF901, supplied by Zhejiang Huafeng New Materials Co., Ltd.

[0033] Epoxidized soybean oil was supplied by Shandong Deyitai New Materials Co., Ltd.; acetyl tributyl citrate was supplied by Condis Chemical (Hubei) Co., Ltd.; tributyl citrate was supplied by Jinan Jiushang New Materials Technology Co., Ltd.

[0034] Example 1

[0035] Prepare the following raw materials according to the mass proportions: 70 parts of PBAT, brand 1200F and T16, including 50 parts of 1200F and 20 parts of T16; 15 parts of PLA, brand F2332; 10 parts of PPC, brand 8801; 10 parts of toughening agent, which needs to be prepared in advance; 10 parts of plasticizer, using tributyl citrate; 2 parts of light stabilizer UV292; 0.3 parts of antioxidant 1098.

[0036] Prepare the toughening agent in advance: add 40kg of gum arabic, 0.04kg of nitrous acid and 0.4kg of silica gel desiccant into a reactor, connect 100kg of phenylalanine and 120kg of tyrosine to a peristaltic pump, connect the peristaltic pump to the reactor, evacuate the reactor and start stirring, heat the reactor to 165°C, and introduce phenylalanine and tyrosine at a uniform speed while stirring for 30 minutes. Continue stirring for 1 hour after the introduction, filter the reaction product in turn, wash with ethanol, sieve to remove the silica gel desiccant, and finally obtain a powdered toughening agent.

[0037] Preparation of biodegradable stretch film: PBAT, PLA, PPC, plasticizer and antioxidant 1098 were stirred at 170°C for 25 minutes, and the prepared toughening agent and light stabilizer UV292 were continued to be added and stirred for 5 minutes; then added to a twin-screw extruder, the barrel temperature was set to 190°C, the head temperature was set to 165°C, and extrusion granulation was performed to obtain a stretch film masterbatch.

[0038] The stretch film masterbatch was added into a single-screw cast film extruder, the barrel temperature was set to 195°C, the head temperature was set to 175°C, and the film was cast and extruded to obtain a biodegradable stretch film.

[0039] Example 2

[0040] Prepare the following raw materials according to the mass proportions: 85 parts of PBAT, brand BT12-203 and T16, including 60 parts of BT12-203 and 25 parts of T16; 10 parts of PLA, brand C2203F; 5 parts of PPC, brand HF901; 15 parts of toughening agent, which needs to be prepared in advance; 5 parts of plasticizer, using acetyl tributyl citrate; 1 part of light stabilizer UV770; 0.1 part of antioxidant 168.

[0041] Prepare the toughening agent in advance: add 70 kg of gum arabic, 0.14 kg of nitrous acid and 2.1 kg of silica gel desiccant into a reactor, connect 100 kg of phenylalanine and 120 kg of tyrosine to a peristaltic pump, and connect the peristaltic pump to the reactor, evacuate the reactor and start stirring, heat the reactor to 170°C, and introduce phenylalanine and tyrosine at a uniform speed while stirring for 20 minutes. After the introduction, continue stirring for 50 minutes, filter the reaction product in turn, wash with ethanol, sieve to remove the silica gel desiccant, and finally obtain a powdered toughening agent.

[0042] Preparation of biodegradable stretch film: PBAT, PLA, PPC, plasticizer and antioxidant 168 were stirred at 165°C for 30 minutes, and the prepared toughening agent and UV770 were continuously added and stirred for 10 minutes; then, the mixture was added to a twin-screw extruder, and the barrel temperature and the head temperature were set to 195°C and 170°C, and extrusion granulation was performed to obtain a stretch film masterbatch.

[0043] The stretch film masterbatch was added into a single-screw cast film extruder, the barrel temperature was set to 190°C, the head temperature was set to 170°C, and the film was cast and extruded to obtain a biodegradable stretch film.

[0044] Example 3

[0045] Prepare the following raw materials according to the mass proportions: 80 parts of PBAT with the brand names 1200F and ECO-A05, including 60 parts of 1200F and 20 parts of ECO-A05; 30 parts of PLA with the brand names C2203F and F2332, including 20 parts of C2203F and 10 parts of F2332; 6 parts of PPC with the brand name 8801; 11 parts of toughening agent, which needs to be prepared in advance; 15 parts of plasticizer, using epoxy soybean oil; 1.5 parts of light stabilizer UV770; and 0.2 parts of antioxidant 1098.

[0046] Prepare the toughening agent in advance: add 50kg of gum arabic, 0.15kg of nitrous acid and 1.0kg of silica gel desiccant into a reactor, connect 100kg of phenylalanine and 120kg of tyrosine to a peristaltic pump, and connect the peristaltic pump to the reactor, evacuate the reactor and start stirring, heat the reactor to 160°C, and introduce phenylalanine and tyrosine at a uniform speed while stirring for 40 minutes. After the introduction, continue stirring for 70 minutes, filter the reaction product in turn, wash with ethanol, and sieve to remove the silica gel desiccant to finally obtain a powdered toughening agent.

[0047] Preparation of biodegradable stretch film: PBAT, PLA, PPC, plasticizer and antioxidant 1098 were stirred at 175°C for 20 minutes, and the prepared toughening agent and UV770 were continued to be added and stirred for 8 minutes; then added to a twin-screw extruder, the barrel temperature was set to 180°C, the head temperature was set to 169°C, and extrusion granulation was performed to obtain a stretch film masterbatch.

[0048] The stretch film masterbatch was added into a single-screw cast film extruder, the barrel temperature was set to 180°C, the head temperature was set to 172°C, and the film was cast and extruded to obtain a biodegradable stretch film.

[0049] Comparative Example 1

[0050] Compared with Example 1, only 10 parts of the toughening agent are replaced by 10 parts of PBAT (1200F), and the remaining components and preparation steps are the same as Example 1.

[0051] Comparative Example 2

[0052] When the toughening agent is prepared in advance, only gum arabic and tyrosine are used for reaction, and phenylalanine is not used for reaction. The remaining components and preparation steps are the same as those in Example 1.

[0053] Comparative Example 3

[0054] When the toughening agent is prepared in advance, only gum arabic and phenylalanine are used for reaction, and tyrosine is not used for reaction. The remaining components and preparation steps are the same as those in Example 1.

[0055] Comparative Example 4

[0056] When the toughening agent is prepared in advance, nitrous acid and silica gel desiccant are not used to participate in the reaction, and the remaining components and preparation steps are the same as in Example 1.

[0057] According to the test standard of GB / T 1040.3-2006, the tensile strength and elongation at break of Examples 1-3 and Comparative Examples 1-4 were tested, and the results are shown in Table 1. The longitudinal direction refers to stretching along the production direction of the biodegradable stretch film (i.e., along the running direction of the machine); the transverse direction refers to stretching perpendicular to the production direction of the biodegradable stretch film (i.e., perpendicular to the running direction of the machine).

[0058]

[0059] No toughening agent is added in Comparative Example 1, and the toughening agent added in Comparative Examples 2-4 is not prepared according to the method of the present invention. According to the data in Table 1, after adding the homemade toughening agent of the present invention, the tensile strength and elongation at break of the biodegradable wrapping film based on PBAT are better than those of Comparative Examples 1-4 in both the transverse and longitudinal directions, that is, the tensile resistance and stretchability are better. In addition, the present invention uses a granulation plus one-time cast extrusion film-making process, which does not require a complex control system and equipment, has a lower processing cost, and is suitable for large-scale production.

[0060] Although the present invention has been described in detail by way of embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, those skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all be within the scope of the present invention.

Claims

1. A biodegradable stretch film, characterized in that: The invention is prepared from the following components in parts by weight: 70-85 parts of polybutylene terephthalate-adipate, 10-30 parts of polylactic acid, 5-10 parts of polypropylene carbonate, 10-15 parts of toughening agent, 5-15 parts of plasticizer, 1-2 parts of light stabilizer, and 0.1-0.3 parts of antioxidant; wherein the toughening agent is prepared by reacting phenylalanine, tyrosine and gum arabic; The mass ratio of phenylalanine, tyrosine and gum arabic is 1:1.2:0.4-0.7; the reaction temperature of phenylalanine, tyrosine and gum arabic is 160-170°C, and the reaction time is 70-110 min; A catalyst and a water absorbent are added during the reaction; the catalyst is nitrous acid, and the added amount is 0.1-0.3% of the mass of gum arabic; the water absorbent is a silica gel desiccant, and the added amount is 1-3% of the mass of gum arabic.

2. The biodegradable stretch film according to claim 1, characterized in that: Polybutylene terephthalate-adipate is one or more of 1200F, BT12-203, T16 or ECO-A05; polylactic acid is one or both of F2332 or C2203F; polypropylene carbonate is one or both of 8801 or HF901; plasticizer is one or more of epoxidized soybean oil, acetyl tributyl citrate, tributyl citrate; light stabilizer is one or both of UV770 or UV292; antioxidant is one or both of antioxidant 168 or antioxidant 1098.

3. A method for preparing the biodegradable stretch film according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Adding phenylalanine, tyrosine, a catalyst and a water absorbent to gum arabic to react and obtain a toughening agent; (2) polybutylene terephthalate-adipate, polylactic acid, polypropylene carbonate, plasticizer and antioxidant are stirred once, and toughening agent and light stabilizer are added for secondary stirring, and then extrusion granulation is performed to finally obtain a stretch film masterbatch; (3) Casting the stretch film masterbatch into a film to produce a biodegradable stretch film.

4. The method for preparing the biodegradable stretch film according to claim 3, characterized in that: In step (2), the first stirring temperature is 165-175°C, the first stirring time is 20-30 min, and the second stirring time is 5-10 min.

5. The method for preparing the biodegradable stretch film according to claim 3, characterized in that: In step (2), a twin-screw extruder is used for extrusion granulation, and the barrel temperature of the twin-screw extruder is 180-195°C and the head temperature is 165-170°C.

6. The method for preparing the biodegradable stretch film according to claim 3, characterized in that: In step (3), a single-screw cast film extruder is used for film casting, and the barrel temperature of the single-screw cast film extruder is 180-195°C, and the head temperature is 170-175°C.

Citation Information

Patent Citations

  • Full-biodegradable wrapping film and preparation method thereof

    CN114656886A

  • Low cost bio-based full degradable film and preparation method thereof

    US20200291225A1